ANALISIS CITRAAN PADA KUMPULAN PUISI PULANG KARYA OKA KUSUMAYUDHA: PENDEKATAN OBJEKTIF - Harita, Maria Magdalena yurnia (Universitas Nias Raya, 2025)
Based on the results of observations made by researchers, there is one image in the collection of poems Pulang by Oka Kusumayudha, namely the image of hearing. Therefore, this research was motivated by the researcher's curiosity about the imagery in the poetry collection Pulang Oka Kusumayudha. The aim of this research is to describe the imagery in Oka Kusumayudha's collection of poetry going home. This type of research is a qualitative approach with descriptive methods. The results of this research show that there are 23 quotes that contain imagery, including; 1) The visual image consists of 7 (seven) quotes, 2) The auditory image consists of 6 (six) quotes, 3) The tactile image consists of 4 (four) quotes, 4) The movement image consists of 5 (five) quotes, and 5 ) The olfactory image consists of 1 (one) quote. So it can be concluded that the Pulang poetry collection contains more visual imagery than other imagery. The suggestions put forward by the researcher are 1) It is hoped that Indonesian language teachers will use this research as reference material, especially in studying literary works. 2) It is hoped that readers will use this research as an additional reference regarding imagery in poetry. 3) It is hoped that future researchers will use this research as a reference in conducting subsequent research.